The adjuvanted recombinant zoster vaccine is efficacious and safe in Asian adults ≥ 50 years of age: a sub-cohort analysis of the ZOE-50 and ZOE-70 randomized trials - Joon Hyung Kim; John Diaz-Decaro; Ning Jiang; Shinn-Jang Hwang; Eun Ju Choo; Maribel Co; Andrew Hastie; David Shu Cheong Hui; Junya Irimajiri; Jacob Lee; Edward Man-Fuk Leung; Haiwen Tang; et al. (Human Vaccines & Immunotherapeutics, 2021)
In two large clinical trials (ZOE-50 [NCT01165177] and ZOE-70 [NCT01165229]), two doses of the adjuvanted recombinant zoster vaccine (RZV) demonstrated >90% efficacy (VE) against herpes zoster (HZ) in adults ≥50 years of age (YOA). This post-hoc analysis assessed the VE against HZ and postherpetic neuralgia (PHN), in participants from Asian study sites enrolled in ZOE-50/70. Reactogenicity and safety were also assessed. Participants ≥50 YOA were randomized 1:1 to receive 2 doses of either RZV or placebo, 2 months apart. VE was evaluated for a median follow-up of 4 years post-vaccination overall and by age in the ZOE-50 Asian population ≥50 YOA and in the pooled ZOE-50/70 Asian population ≥70 YOA. Of the 2,729 participants included in the ZOE-50 Asian population ≥50 YOA, 3 RZV and 66 placebo recipients reported a confirmed HZ episode. Overall VE was 95.6% (95% confidence interval [CI]: 86.4–99.1) against HZ and 100% (95% CI: 35.44–100) against PHN. In the pooled ZOE-50/70 Asian population ≥70 YOA, 4 RZV and 75 placebo recipients out of the 2,723 participants reported a confirmed HZ episode. Overall VE was 94.7% (95% CI: 85.9–98.6) against HZ and 89.8% (95% CI: 28.39–99.77) against PHN. Pain and myalgia were the most frequent solicited local and general adverse events, respectively, in both populations. No safety concern was identified during the study periods. RZV is highly efficacious against HZ and PHN and has an acceptable safety profile in Asian populations ≥50 YOA, similar to what was observed in the general ZOE-50/70 populations. Trademark statement: Shingrix is a trademark owned by or licensed to the GSK group of companies.